2023
DOI: 10.14336/ad.2023.0308
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor Protein: A Regulatory Hub in Alzheimer's Disease

Abstract: Decades of research have demonstrated an incontrovertible role of amyloid-β (Aβ) in the etiology of Alzheimer's disease (AD). However, the overemphasis on the pathological impacts of Aβ may obscure the role of its metabolic precursor, amyloid precursor protein (APP), as a significant hub in the occurrence and progression of AD. The complicated enzymatic processing, ubiquitous receptor-like properties, and abundant expression of APP in the brain, as well as its close links with systemic metabolism, mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 210 publications
0
6
0
Order By: Relevance
“…DNPZ is known to inhibit the activity of BuChE and ADA, reduce LP and increase NO levels, and enhance antioxidant status. It also regulates the endocytic trafficking of APP by upregulating the expression of sorting nexin protein-33 (SNX33) [ 49 , 50 ]. The present study showed that the two lead compounds, and in particular 3c , have AChE inhibitory and antioxidant activity comparable to the reference drug DNPZ in the mouse SC model.…”
Section: Discussionmentioning
confidence: 99%
“…DNPZ is known to inhibit the activity of BuChE and ADA, reduce LP and increase NO levels, and enhance antioxidant status. It also regulates the endocytic trafficking of APP by upregulating the expression of sorting nexin protein-33 (SNX33) [ 49 , 50 ]. The present study showed that the two lead compounds, and in particular 3c , have AChE inhibitory and antioxidant activity comparable to the reference drug DNPZ in the mouse SC model.…”
Section: Discussionmentioning
confidence: 99%
“…Two examples include APP and PIAS1. The protein encoded by APP is essential to the pathophysiology of Alzheimer’s Disease [ 58 ]. There are also data indicating that this protein, or fragments of it, have anti-viral properties against IAV as well as other viruses [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in the amyloidogenic pathway, β-secretase cleaves APP at the N-terminus of the Aβ sequence, originating sAPPβ and transmembrane βCTF. Therefore, upon the subsequent action of γ-secretase, the cleavage of βCTF, but not that of αCTF, results in the production of Aβ [ 23 , 24 ]. The processing of βCTF by γ-secretase occurs at different sites, thus yielding many Aβ peptides of variable length, with Aβ 40 being the most abundant form in the brain, followed by Aβ 38 and Aβ 42 [ 25 ].…”
Section: The Amyloid Cascade Hypothesis: From Plaques To Soluble Olig...mentioning
confidence: 99%